Implementation of Merdeka Curriculum: The Role of Islamic Education Lesson in Shaping the Pancasila Student Profile - Mulyadi, Acep; Ramadhani, Muhammad Syakhil Afkar (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2024)
The purpose of this study is to determine and describe the role of the Islamic Education class X lesson based on the Merdeka Curriculum in shaping the Pancasila Student Profile at SMA Negeri 1 Tambun Selatan. As for the implementation of the Merdeka Curriculum, the problems of implementing the Merdeka Curriculum, and the efforts made by schools and PAI teachers in overcoming the problems of implementing the Merdeka Curriculum. The research method used is a qualitative method with a descriptive approach. The results of this study indicate that the Merdeka Curriculum can form the Pancasila Student Profile in class X PAI lessons at SMA Negeri 1 Tambun Selatan. This is evidenced by data from resource persons, namely the Principal, Deputy Head of Curriculum, PAI Teacher, Grade X students, and reinforced by relevant theories. In addition, the teacher in learning PAI class X is in accordance with the teaching module that adapts to the CP and ATP of the Ministry of Education and Culture. There are obstacles experienced by class X PAI teachers when implementing the Merdeka Curriculum, namely less than optimal differentiated learning and less than optimal intracurricular learning. Efforts that need to be made in overcoming these obstacles, namely Teacher readiness in implementing the Merdeka Curriculum, determining the learning methods and strategies to be used, discussion and collaboration among teachers. These efforts are expected to be a solution to overcome the problems that occur in implementing the Merdeka Curriculum.